Vladimir Nabokov Poetry and the Lyric Voice - Morris, Paul D. (University of Toronto Press, 2017)
Vladimir Nabokov (1899-1977), the eminent Russian-American writer and intellectual, is best known for his novels, though he was also the author of plays, poems, and short stories. In this important new work, Paul D. Morris offers a comprehensive reading of Nabokov's Russian and English poetry, until now a neglected facet of his oeuvre. Morris' unique and insightful study re-evaluates Nabokov's poetry and demonstrates that poetry was in fact central to his identity as an author and was the source of his distinctive authorial - lyric - voice.After offering a critical overview of the multi-staged history of the reception of Nabokov's poetry and an extensive analysis of his poetic writing, Morris argues that Nabokov's poetry has largely been misinterpreted and its place in his oeuvre misunderstood. Through a detailed examination of the form and content of Nabokov's writings, Morris demonstrates that Nabokov's innovations in the realms of drama, the short story, and the novel were profoundly shaped by his lyric sensibility
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: Nabokov, Vladimir Vladimirovič -- 1899-1977; DISCOUNT-B.; Lyrik; Hochschulschrift